ATP is required for interactions between UAP56 and two conserved mRNA export proteins, Aly and CIP29, to assemble the TREX complex - Dufu, Kobina (Cold Spring Harbor Laboratory Press, 2010)
The conserved TREX mRNA export complex is known to contain UAP56, Aly, Tex1, and the THO complex. Here, we carried out proteomic analysis of immunopurified human TREX complex and identified the protein CIP29 as the only new component with a clear yeast relative (known as Tho1). Tho1 is known to function in mRNA export, and we provide evidence that CIP29 likewise functions in this process. Like the known TREX components, a portion of CIP29 localizes in nuclear speckle domains, and its efficient recruitment to mRNA is both splicing- and cap-dependent. We show that UAP56 mediates an ATP-dependent interaction between the THO complex and both CIP29 and Aly, indicating that TREX assembly is ATP-dependent. Using recombinant proteins expressed in Escherichia coli, we show that UAP56, Aly, and CIP29 form an ATP-dependent trimeric complex, and UAP56 bridges the interaction between CIP29 and Aly. We conclude that the interaction of two conserved export proteins, CIP29 and Aly, with UAP56 is strictly regulated by ATP during assembly of the TREX complex.